IMPLEMENTASI PERLINDUNGAN HUKUM TERHADAP KONSUMEN PEMERIKASAAN MATA PADA OPTIKAL YANG TIDAK MEMILIKI TENAGA REFRAKSIONIS OPTISIEN DI KOTA PEKANBARU - Erwin Ramadan; Maryati Bachtiar; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Humans as living things have various needs. Today, human needs are increasingly varied andthings that were not too important have become very important. Examples can be seen in everyday life,namely handheld smartphones, laptops and televisions. Almost all aspects use the item. The increasing needfor these items can have a negative effect on eye health. Besides the bad habits of watching television toolong, staring at a laptop screen or taking too long a smartphone which is an electronic digital device canpotentially cause interference with vision (refraction abnormalities).This study is a sociological juridical legal research, what is meant by sociological juridicalresearch is an approach by looking in terms of legislation and the reality that occurs in the field, inaccordance with the formulation of the problems expressed by the author. . While the population and sampleare parties related to the problems examined in this study, the data sources used, primary data, secondarydata, and tertiary data. The technique of collecting data in this study was through interviews and literaturereview.From the results of the research that the authors did, it can be concluded, first the implementationof legal protection against consumers eye examination on Optics who do not have Optional Refractionists inPekanbaru, namely: still not optimally implemented, there are still many optics that perform eyeexamination without Optional Refraction, the second is the Optical Responsibility of consumers of eyeexaminations at Optics who do not have Optional Refraction in the City of Pekanbaru, namely: there arestill many Optics that have not provided maximum accountability.Keywords : Implementation - Legal Protection - Eye Examination - Optional Refraction Power.